Adaptation of running pattern to the drop of standard cushioned shoes: A randomised controlled trial with a 6-month follow-up. Issue 8 (August 2017) - Malisoux, Laurent; Gette, Paul; Chambon, Nicolas; Urhausen, Axel; Theisen, Daniel
Abstract: Objectives: While several cross-sectional studies have investigated the acute effects of shoe drop on running biomechanics, the long-term consequences are currently unknown. This study aimed to investigate if the drop of standard cushioned shoes induces specific adaptations in running technique over a six-month period in leisure-time runners. Design: Double-blinded randomised controlled trial. Methods: The participants (n = 59) received a pair of shoes with a heel-to-toe drop of 10 mm (D10), 6 mm (D6) or 0 mm (D0) and were followed-up regarding running training over 6 months or 500 km, whichever came first. Spatio-temporal variables and kinematics (foot/ground, ankle and knee joint angles) were investigated while running at preferred speed on a treadmill before and after the follow-up. Results: The participants ran 332 ± 178 km in the study shoes between pre- and post-tests. There was no shoe version by time interaction for any of the spatio-temporal variables nor for lower limb angles at initial ground contact. A small but significant shoe drop effect was found for knee abduction at mid-stance (p = 0.032), as it decreased for the D0 version (−0.3 ± 3.1 vs. −1.3 ± 2.6°) while it increased for the D6 (0.3 ± 2.7 vs. 1.3 ± 3.1°) and D10 version (-0.2 ± 3.2 vs. 0.5 ± 3.1°). However, none of the pairwise comparisons was significant in the post-hoc analysis. Conclusions: Apart from knee abduction at mid-stance, no specific adaptation in spatio-temporal variables and kinematics was found between the three shoe versions during this 6-month follow-up. Thus, shoe drop of standard cushioned shoes does not seem to influence running biomechanics in the long term.